Energy availability estimated in free-living conditions positively correlates with peak progesterone concentration in the menstrual cycle of race walkers and runners not using hormonal contraception - Castellanos-Mendoza, M. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Low energy availability [EA] alters luteinizing hormone [LH] and oestradiol, important menstrual cycle [MC] regulators. The aim was to determine the relationship between EA estimated in free-living conditions and peak serum progesterone concentration [Pk-PRG], as the ovulatory status indicator of MCs. Subjects were 8 race walkers and 9 runners of recreational-world competitive level, 47-109 km·week-1 training volume, 14-41 years old, 1.5-27 years after menarche, 39.5-61.5 kg body mass, 1.39-1.74 m height, and 71-162 mm ?8 skinfolds [methodology of the International Society for the Advancement of Kinanthropometry]. Twenty-one MCs were analysed. Seven-day average EA was estimated, within the follicular phase of each MC, from food and training & physical activity logs. Individual urine LH-peak day, predicted MC length and basal body temperature changes were considered to schedule progesterone determination at peak period. Serum progesterone was determined by electrochemiluminescence immunoassay with Cobas e601. EA correlates with Pk-PRG [r(19) = .72, 95% CI: .41-.88; p < .001; 1 - ß = .99]. EA of cycles with optimal [>10 ng·mL-1] was higher than EA of cycles with anovulatory [<5.8 ng·mL-1] Pk-PRG [one-way ANOVA, 1 - ß = .84; Tukey`s p = .008]: 40.0 ± 4.5 [n = 8] vs. 30.3 ± 2.9 [n = 4] Kcal·Kg FFM-1·day-1. Ovulatory disturbances [Pk-PRG =10 ng·mL-1] were observed with EA =36 kcal·Kg FFM-1·day-1. Female athletes not using hormonal contraception should monitor the ovulatory status of their MCs, otherwise aim for EA >36 kcal·Kg FFM-1·day-1 -estimated with methods used herein.